Comparisons of Student's Self-Learning Performances Using Java and Kotlin Languages in Android Programming Learning Assistance System - Syaifudin, Yan Watequlis; Funabiki, Nobuo; Liem, Inggriani (2021 1st Conference on Online Teaching for Mobile Education (OT4ME), 2021)
Along with the recent popularity of Android smartphones, the demand for Android application developers in the entire world also increased significantly. In the previous study, Android Programming Learning Assistance System (APLAS) has been proposed as a self-learning platform for Android application development using Java language in http://aplas.polinema.ac.id. Different from other self-learning platforms, it offers a self-learning model by adopting test-driven development (TDD) method. Then, since Google announced Kotlin becomes recommended language for Android Studio, APLAS has been improved to accommodate this language. This paper presents the comparisons of student's learning performances using Java and Kotlin languages in APLAS. The results confirmed the support of APLAS for self-learning in the two languages. Most students tended to use Java because they were more familiar with this language as the standard language of object-oriented programming course. However, the students who used Kotlin showed better performance and faster adaptation.